The return to training and competition after Achilles tendon injuries - Kroesche, S. (New Studies in Athletics, 2009)
Achilles tendon problems comprise a complex of complaints wide-spread in sport, particularly among athletes in the running and jumping events. In an accompanying article, the author provided descriptions from the current sports medicine literature of the biomechanics of the Achilles tendon, the main problems that affect it, the mechanisms at work in injuries and the factors that must be taken into account in the prevention of such injuries and conditions. Drawing on the same literature, this article addresses the rehabilitation that is necessary for an athlete to return to training and competition while minimising the risk of re-injury. The aim is to provide practical information that will be of value to therapists, coaches and athletes as they to work together to plan and structure individualised rehabilitation programmes. It contains an overview of the main types of measures used in the rehabilitation of Achilles tendon injuries and conditions, including training, physical and therapeutic, conditioning, biomechanical and local pharmaceutical means. It then gives abstracts of therapeutic concepts in which these measures are employed that have been developed by five authors. The article concludes with some general advice on the design and implementation of a rehabilitation programme.